With A Little Help From My Enemy: Comparative Advertising - Francesca Barigozzi; Paolo Garella; Martin Peitz (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
Comparative advertising content diers from generic. We discover that dissipative advertising has consequences depending upon content and cost. Comparison advertising may trigger legal action by rival …rms that are named. In the model an entrant signals its product quality. By a comparative ad the entrant refers to the incumbent's product. We show that comparison can enhance the signaling potential of dissipative advertising. From the viewpoint of the entrant, the choice of comparative advertising empowers the rival with the right to sue; generic does not. Consumers therefore infer that if the entrant uses comparative instead of generic ads it has a strong case.
Keywords: 330